Studi Komparasi Kesiapan Indonesia Menerapkan Carbon Trade 2025 - Ferdiansyah, Muhammad Rayhan Ali; Rosyadah, Hanif; Ramadhan, Fikri Fajar (UI Scholars Hub, 2025)
This study aims to assess Indonesia’s readiness to implement carbon trading in 2025 to achieve net zero emissions by 2060. The research uses a mixed-method approach, combining literature review, multivariate linear regression, and Vector Error Correction Model (VECM). The results indicate that the Human Development Index (HDI) has a negative and significant impact on CO2 emissions in the long term. This impact is greater than the results observed in Singapore and Thailand. With established policies and a demographic bonus in 2045, optimizing human resources is crucial for achieving net zero emissions by 2060.